2009
DOI: 10.1177/1538574408324510
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hyperperfusion After Carotid Stenting: A Transcranial Doppler and SPECT Study

Abstract: Symptomatic cerebral hyperperfusion is not uncommon after carotid stenting. There seems to be a link between exhausted cerebrovascular reactivity of the ipsilateral middle cerebral artery and increased risk of cerebral hyperperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However Sfyroeras et al did not find an association between preoperative asymmetry in brain perfusion in rest and CHS. 68 Ogasawara et al suggested that hyperperfusion lasting at least to the three postoperative days on SPECT predisposes to CHS development. 69 Advanced imaging processes and statistical analyses can further improve the predictive value of this technique.…”
Section: Investigatory Techniques In Prediction and Diagnosis Of Chsmentioning
confidence: 99%
“…However Sfyroeras et al did not find an association between preoperative asymmetry in brain perfusion in rest and CHS. 68 Ogasawara et al suggested that hyperperfusion lasting at least to the three postoperative days on SPECT predisposes to CHS development. 69 Advanced imaging processes and statistical analyses can further improve the predictive value of this technique.…”
Section: Investigatory Techniques In Prediction and Diagnosis Of Chsmentioning
confidence: 99%
“…This finding is probably due to an improvement in vasodilatory ability, indicating return of vascular reserve capacity. Although such patients may benefit from greater hemodynamic improvements, hyperperfusion is still a concern that can lead to hemorrhage [75]. In fact, a condition called cerebral hyperperfusion syndrome (CHS) after carotid intervention has been classically described as an acute neurologic deficit occurring from hours to days following a carotid procedure and represents a spectrum of clinical symptoms ranging from severe unilateral headache, to seizures and focal neurologic defects, to intracerebral hemorrhage in its most severe form.…”
Section: Cvr Mapping With Boldmentioning
confidence: 99%
“…TCD has, in fact, been proven useful in the prediction of these complications. 40,41 Computed tomography and magnetic resonance angiography. With the increasing utilization of noninvasive imaging studies such as CTA and MRA prior to carotid interventions, standardization of the reporting of imaging findings is necessary.…”
Section: Diagnostic Imaging Studiesmentioning
confidence: 99%